Insight into the role of biogenic manganese oxides-assisted gravity-driven membrane filtration systems toward emerging contaminants removal. (1st October 2022) - Chen, Rui; Zhang, Han; Wang, Jinlong; Xu, Daliang; Tang, Xiaobin; Gong, Weijia; Liang, Heng
Highlights: Pollutant elimination and stable flux were improved in BioMnOx-GDM. BioMnOx with strong oxidating capacity and activity promoted pollutant removal. More abundant bacteria with high biological activity were observed in BioMnOx-GDM. BioMnOx-GDM facilitated the removal of SMX and ARGs. Biofilm with high porosity and low LB-EPS concentration promoted flux increase. Abstract: Effective water purification technologies are required to remove emerging contaminants (ECs) and prevent their extensive occurrence in rural areas. In this work, coupling gravity-driven membrane (GDM) filtration with biogenic manganese oxides (BioMnOx) in the biofouling layer was utilized for treating water containing SMX. Comparisons between BioMnOx-GDM (with BioMnOx) and Control-GDM (without BioMnOx) indicated that BioMnOx could significantly promote the removal of DOC, NH4 + -N, and fluorescent pollutants due to its strong oxidating capacity and high biological activity. The formation of BioMnOx increased the abundance of SMX-degrading bacteria, enriched the metabolic pathway and mineralization rate of SMX, and effectively promoted the remove of SMX. More importantly, BioMnOx facilitated the removal of antibiotic resistance genes (ARGs) in the GDM, because it increased the link between microorganisms and reduced the concentration of SMX, thus reduced the expression of ARGs. LB-EPS played an important role in the membrane fouling. Compared with the Control-GDM, the concentration of LB-EPS in BioMnOx-GDM decreased, which was beneficial to alleviate membrane fouling. Although a thicker biofouling layer (1774.88 μm vs.775.54 μm) was formed in BioMnOx-GDM, the biofilm with higher porosity (64.93% vs. 41.24%) had a more positive effect on the flux. Overall, BioMnOx could improve the pollutant removal and stable flux level of the GDM system. BioMnOx-GDM effectively avoided the risks brought by ECs and ensured water safety in rural areas. Graphical abstact\: Image, graphical abstract